Phenotypic and Genotypic Characterization of Bacteria from Diabetic Ulcers: Insights into Resistance and Biofilm Formation - Ernawati, Andi; Rusmana, Iman; Wahyudi, Aris Tri; Murtini, Sri; Budiarti, Sri (Journal of Multidisciplinary Applied Natural Science, 2026)
Diabetic ulcers are prone to colonization by multidrug-resistant bacteria, complicating treatment and recovery. Therefore, understanding the microbial profile and resistance mechanisms is essential for effective clinical management. This study isolated and characterized bacteria from diabetic ulcer patients in West Java, Indonesia. Identification was performed using the selective differential medium test and 16S rRNA sequencing. Antibiotic susceptibility was assessed via the disc diffusion method, and biofilm formation was evaluated using crystal violet staining. PCR amplification targeted blaTEM and sul1 resistance genes. A total of 15 bacterial isolates were identified, predominantly Staphylococcus aureus and Pseudomonas aeruginosa. Six isolates exhibited a multiple antibiotic resistance (MAR) index >0.4 and demonstrated biofilm-forming capacity. The PCR result confirmed the presence of blaTEM and sul1 genes in three isolates. The findings highlight the prevalence of multidrug-resistant, biofilm-forming bacteria in diabetic ulcers, underscoring the need for targeted antimicrobial strategies and resistance monitoring.